Optimization of the Hockey Fans in Training (Hockey FIT) weight loss and healthy lifestyle program for male hockey fans - Wendy Blunt; Dawn P. Gill; Shannon L. Sibbald; Brendan Riggin; Roseanne W. Pulford; Ryan Scott; Karen Danylchuk; Cindy M. Gray; Sally Wyke; Christopher Bunn; Robert J. Petrella (BMC, 2017)
Abstract Background The health outcomes of men continue to be poorer than women globally. Challenges in addressing this problem include difficulties engaging men in weight loss programs as they tend to view these programs as contrary to the masculine narrative of independence and self-reliance. Researchers have been turning towards sports fans to engage men in health promotion programs as sports fans are typically male, and tend to have poor health habits. Methods Developed from the highly successful gender-sensitized Football Fans in Training program, Hockey Fans in Training (Hockey FIT) recruited 80 male hockey fans of the London Knights and Sarnia Sting who were overweight or obese into a weekly, 90-minute classroom education and group exercise program held over 12 weeks; a 40-week minimally-supported phase followed. A process evaluation of the Hockey FIT program was completed alongside a pragmatic randomized controlled trial and outcome evaluation in order to fully explore the acceptability of the Hockey FIT program from the perspectives of coaches delivering and participants engaged in the program. Data sources included attendance records, participant focus groups, coach interviews, assessment of fidelity (program observations and post-session coach reflections), and 12-month participant interviews. Results Coaches enjoyed delivering the program and found it simple to deliver. Men valued being among others of similar body shape and similar weight loss goals, and found the knowledge they gained through the program helped them to make and maintain health behaviour changes. Suggested improvements include having more hockey-related information and activities, greater flexibility with timing of program delivery, and greater promotion of technology support tools. Conclusions We confirmed Hockey FIT was an acceptable "gender-sensitized" health promotion program for male hockey fans who were overweight or obese. Minor changes were required for optimization, which will be evaluated in a future definitive trial. Trial registration NCT02396524 (Clinicaltrials.gov). Date of registration: Feb 26, 2015.